Novel Sustainable Optimal Marine Microgrid Active-Power Management and Control Including Hybrid Power Generation and Multiple-Energy Storage Devices - Aimad Boudoucha; Nour El Yakine Kouba; Sara Touhant; Yasmine Saidoune (Engineering Proceedings, 2024)
This paper deals with the design of an advanced optimal strategy to enhance power management and frequency control in marine microgrids. The investigated system incorporates a mix of renewable energy sources coordinated with hybrid energy storage devices. A new robust optimal PIDN controller is employed to tackle the intermittency challenges associated with wind and marine power generation, ensuring precise frequency control via time-domain simulations. A multiple-energy storage system, which includes SMES/batteries/ultra-capacitors (UCs) and fuel cells (FCs), was implemented to manage frequency variations and optimize the charge/discharge cycles of batteries. To further mitigate power fluctuations and extend the life of batteries, a low-pass filter was applied, inspired by optimization techniques for hybrid storage systems. A notable innovation of this study is the introduction of an offshore photovoltaic (PV) array into the system, enhancing the diversity and capacity for renewable energy production in the microgrid. A comprehensive comparative study was conducted, exploring a range of scenarios: with and without energy storage, with the integration of PV energy, excluding the use of diesel, and implementing battery filtering. This approach allowed for an evaluation of the impact of each configuration on the overall performance of the marine microgrid, underscoring significant enhancements in sustainability, efficiency, and a reduction in the dependence on fossil fuels. Preliminary results point to a considerable improvement in the energy management of isolated marine environments, showcasing the potential of this strategy for future marine microgrid applications. This research makes a significant contribution to the advancement of renewable energy management systems, presenting a viable and sustainable option for powering marine microgrids.